Representasi Konteks Sejarah dalam Puisi Esai Mata Luka Sengkon Karta - Rully Adriansyah; Tanti Agustiani (Imajeri: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
This study aims to describe how historical contexts contained in the essay poem "Mata Luka Sengkon Karta" by Peri Sandi Huizche. With reference to some problem formulations formulated on how the historical context is presented and how social criticism in the essay poem "Mata Luka Sengkon Karta" by Peri Sandi Huizche. The method used is a descriptive qualitative method using data collection techniques namely interventarization techniques, reading reading techniques, recording techniques. Based on research conducted by researchers, it can be concluded that there are three historical contexts and three social criticisms contained in the essay poem "Mata Luka Sengkon Karta" by Peri. Keywords: Historical Contexts; Essay Poem; Mata Luka Sengkon Karta